The Impact of COVID-19 Pandemic on Tuberculosis Patient Treatment Adherence - Natalia Christin Tiara Revita; Tintin Sukartini; Makhfudli Makhfudli; Joel Rey Ugsang Acob; Hasanudin Hasanudin; Handira Nadhifatul Aini (Jurnal Respirasi, 2022)
Coronavirus disease 2019 (COVID-19) pandemic caused a lack of attention to treatment of tuberculosis (TB). TB patients who do not adhere to treatment during a pandemic can cause various health problems in various countries. COVID-19 pandemic adversely affects TB patients such as increasing psychological stress, triggering non-adherence to treatment, affecting quality of life, and even increasing the number of deaths of TB patients. The increasing number of deaths and decreasing success of TB treatment during the pandemic are serious problems that must be addressed immediately. Various efforts were made to overcome the barriers for TB treatment during pandemics. Health workers can provide health education and rehabilitation programs in another media such as tele-health. Digital media can provide health information about TB, improve medication adherence, emphasize the benefits of medication adherence, and motivate patients to undergo treatment.